Tukia : mā te hē ka tika : Māori social workers' experiences of the collision of their personal, professional and cultural worlds : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Te Kunenga ki Pūrehuroa (Massey University, Manawatū), Aotearoa (New Zealand) - Watson, Andrea Makere (Massey University, 2017)
Reamer (2013a) states that the most difficult ethical dilemmas happen for social workers when their personal and professional worlds conflict. Māori social workers (kaimahi) often live and work in the same area as their whānau, hapū and iwi and there is a high chance that members of their whānau will come through the organisation that they work for. This is when kaimahi will experience a collision (tukia) of their personal, professional and cultural worlds. It is the domain where the three different systems have to interact – a professional system, a whānau system, and a cultural system. This research study interviewed seven kaimahi who had experienced tukia and explored their encounter of tukia. Kaupapa Māori underpins this research, and pūrakau has been utilised to connect the research to Māori worldviews, however the research framework is guided by the Pā Harakeke. Pā Harakeke is often used as a metaphor for whānau and a model for protection of children, whānau structure and well-being. The harakeke sits well in this research as the focus is on the well-being of kaimahi Māori – caring for the carers, helping the helpers and healing the healers. Hence the kaimahi represents the rito (baby centre shoot) of the harakeke, needing nurture, help and support. A key finding from this study reveals that collision is a complex area that requires careful navigation by the kaimahi experiencing the collision, as well as the organisation that the kaimahi works for. It is imperative that social workers and managers discuss and plan for collision as opposed to waiting until it happens, and organisations should have policies and protocols in place for working with whānau. This research has also developed a definition and construction of what collision is in the social services and kaimahi have imparted words of wisdom (Ngā Kupu Taonga) so that others experiencing collision may find a way forward. These include: Take care of the ‘self’, get good support from whānau and mahi, talk about the hard stuff, get good supervision, come back to reality and smell the manuka (be grounded), and the collision can ultimately be a growth experience that will have a positive impact on kaimahi practice.
Māori social workers' experiences of the collision of their personal, professional and cultural worlds
Keywords: Minority social workers; Māori social workers; Social workers; Maori; Services for; New Zealand; Toko i te ora; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social work